Lettuce production in a greenhouse under fertigation with nitrogen and potassium silicate (Acta Scientiarum. Agronomy, 2017)
The objective of this study was to evaluate the effect of nitrogen and potassium silicate on the production and commercial aspects of curly lettuce, Vera cultivar. The experimental design was completely randomized (CRD), with ten treatments and three replications. The treatments, arranged in a factorial design according to the Plan Puebla III matrix (Turrent & Laird, 1975), consisted of the combination of five doses of nitrogen (9; 54; 90; 126, and 171 kg ha-1) and five doses of potassium silicate (1.15; 6.90; 11.50; 16.10, and 21.85 kg ha-1). A control treatment without application of nitrogen and potassium silicate was also inserted. The crop was grown in a greenhouse, and the doses were applied as sidedressing using a drip micro-irrigation system. Total fresh matter, commercial fresh matter, non-commercial fresh matter, number of leaves and commercial trade index were evaluated. The commercial fresh matter and the number of commercial leaves per plant were affected only by nitrogen fertigation and increased linearly with an increase in the dose of nitrogen, with the best responses observed at the highest dose of this element (171 kg ha-1). Potassium silicate only had an effect on non-commercial fresh matter, with no influence on the other characteristics.